Application of the TPACK Approach in Increasing Student Learning Activity Through the PBL Model in Mathematics Learning in Class V Elementary Schools - Mustika, Laura; Yantoro, Yantoro; Sastrawati, Eka (FKIP - Universitas Riau, 2024)
This research was motivated by the low learning activity of class V students at SDN 131/IV Jambi City. This research is classroom action research which aims to describe how the Technological Pedagogical And Content Knowledge (TPACK) approach is implemented in increasing student learning activity through the PBL model in class V of elementary schools. This research was carried out at SDN 131/IV Jambi City. The data in this research was obtained by observation and documentation. The data in this research was analyzed descriptively qualitatively. The research results show that applying the TPACK approach in the mathematics learning process can increase student learning activity. This increase can be seen in the data analysis for each meeting cycle, where for cycles I, meetings I and II, it was 65.74%, for cycles II, meetings I and II, it was 82.22%. Therefore, it can be concluded that the application of the TPACK approach through the PBL model can increase student learning activeness in mathematics learning in class V at SDN 131/IV Jambi City. This is proven by the increase in student learning activity in each cycle by using the TPACK approach through the PBL model.